Ellipsometry of hydrous platinum oxide layers and electrodispersed platinum surfaces resulting from their electroreduction - Zerbino, Jorge Omar (1993)
The ellipsometric characteristics of relatively thick hydrous Pt oxide layers (HPtOLs) produced by oxidation- reduction cycling in the 0–2.4 V range in 1 M H2SO4, and the surface topography of electrodispersed Pt electrodes (EDPtEs) obtained by electroreducing the HPtOLs have been determined in the 400–700 nm range at 25 °C. The HPtOL is light absorbing and can be described as a layer made up of H2O and Pt oxide. The water content increases with increasing layer thickness, approaching a PttO2-to-H2O molar ratio of about 4. The EDPtE resulting from the slow electroreduction of HPtOL can be described as a rough structure with a metal-to-void ratio close to 0.5, which is consistent with a brush-like geometry.